OP0204-PC Multisite Peripheral Joint Pain in the Community: Prevalence and Impact in the North West Midlands, United Kingdom (UK). (23rd January 2014) - Finney, A.; Healey, E. L.; Lewis, M.; Ryan, S.; Dziedzic, K. S.
Abstract : Background: Current research and guidelines are often focused on single joint osteoarthritis (OA). The National Institute for Health and Clinical Excellence OA guidelines recommended that future research should consider the impact of multisite joint pain (NICE, 2008). Objectives: To describe the prevalence and pattern of multisite joint pain (pain in two or more joint sites; hip, knee, hand, foot) and the impact on quality of life (QoL) and general health in a community dwelling population. Methods: A cross-sectional population survey was mailed to adults aged 45 years and over (n=28, 443) registered with 8 general practices in the North West Midlands, UK as part of the MOSAICS study. Participants provided information on demographic characteristics, general health, QoL and joint pain in the hand, hip, knee or foot in the last year. Participants were divided into mutually exclusive subgroups based on 16 combinations of multisite joint pain. These subgroups were collapsed into five groups based on the number of pain sites: 0, 1, 2, 3 and 4. Linear regression analysis was used to investigate the association of multisite joint pain with general health (SF12, PCS & MCS) and QoL (EQ5D) after adjusting for age, gender, BMI, and social deprivation. Results: Of those mailed the survey, it was completed by 15, 083 (53.0%). Average age of responders was 63.9 years (11.2 sd) and approximately half were female. 11, 928 (42.0%) had joint pain, 8206 (28.8%) had multisite joint pain. Knee pain was the most prevalent single site pain (n=1492, 5.2%). Knee and hand was the most prevalent combination of 2 sites of joint pain (n=857, 3.0%) and knee, hand and foot was the most prevalent of 3 sites of joint pain (n=712, 2.5%). The prevalence of pain in all four sites was n=1953 (6.9%). After adjusting for covariates the linear regression showed a statistically significant association between multisite joint pain and the EQ5D and SF12. Each additional joint site demonstrated an increasing negative impact on QoL and general health (see table 1 .) Table 1 . The impact of multisite joint pain on the EQ5D and SF12 Conclusions: Self-reported multisite peripheral joint pain has a significant negative impact on general health and QoL in the community. Multisite joint pain also shows a greater impact with each additional affected joint site. These findings suggest that the impact of multisite joint pain should be assessed in consultations with health care professionals. References: NICE (2008) Osteoarthritis. The care and management of osteoarthritis in adults. National practice guideline no 59. London: NICE. Disclosure of Interest: None Declared